Novel multi-physics simulation of transient dynamics in functionally graded porous multiferroic cylindrical shells under moving heat flux: A magneto-electro-thermoelastic analysis - Tarkashvand, A.; Zafari, H.; Aliakbari, F. (Engineering structures, 2025)
Cylindrical structures, such as pipelines in power plants and novel energy-harvesting devices that combine flexible piezoelectric/piezomagnetic layers with other materials, are frequently exposed to moving heat fluxes. Understanding the physics of these structures can provide potential solutions for stress management and energy harvesting. This study investigates, for the first time, the effect of thermal wave propagation on the transient fully coupled magneto-electro-thermoelastic (METE) response of functionally graded porous (FGP) multiferroic cylindrical shells subjected to a partially distributed moving heat flux. The structure is supported by a distributed viscoelastic Winkler-Pasternak foundation, and its mechanical and electromagnetic boundary conditions are considered to be simply supported and suitably grounded. This approach is innovative as it represents the first extension of the three-dimensional (3D) Lord-Shulman coupled thermoelasticity theory to specifically address multiphysics materials. In this updated framework, the governing equations for the motion of each layer are derived following an orthotropic laminated model. To solve the problem, the state-space technique and the mathematical model of the transfer matrix are employed. The study evaluates the structure's vibrational behavior by examining four models of porosity distributions within the thermoelastic layer: symmetric, stiff non-symmetric, soft non-symmetric, and uniform. The key parameters of the dynamic response are calculated using Durbin’s numerical Laplace inversion algorithm. Subsequently, to validate the proposed model, the results are compared with the findings obtained by other researchers. Comprehensive numerical results concerning temporal and spatial variations of temperature, transverse displacement, and stress components are presented for various influencing parameters such as volume fraction index, open or closed-circuit conditions, heat flux speed, porosity, and smart layer thickness. [Display omitted] •Transient fully coupled thermoelastic response of the porous multiferroic cylinders under a moving heat flux is investigated.•Lord Shulman's theory is extended to show wave-like thermal propagation in multiphysics materials for the first time.•Using Durbin's Laplace inversion algorithm, a state-space method is offered based on piezo-magneto-thermo-elasticity theory.•Four models of porosity distributions to assess the structure's vibrational behavior are studied.•The computational framework leads to efficient design and control of hybrid and smart structures under thermal stress.